Open Innovation in E-Procurement Implementation at PT AL - Umam, Gumay Khotibul; Kusumastuti, Retno (Budapest International Research and Critics University, 2021)
PT AL is a leading company in Indonesia in the field of Datacom, Telecommunications, and ICT for more than 30 years. Companies in this field prefer external parties compared to internal parties in developing e-procurement systems. This study reveals how open innovation is implemented in an e-procurement system and how open innovation in e-procurement implementation must be adjusted by the organization's internal regulations. The purpose of this study is to provide an in-depth analysis of how private companies use e-procurement implementation and how open innovation is carried out on the e-procurement system. This research was conducted with a qualitative approach and the type of research was ethnography, the authors made observations, field notes, and in-depth interviews with company structures and partners who helped develop the system. The results of this study indicate that open innovation can affect the company's operational performance. Furthermore, open innovation is an internal consideration for developing the system because it becomes more practical and there is an exchange of knowledge between the two parties. This research can provide benefits to the academic and practical world, especially the theme of open innovation of e-procurement systems in private companies.